SYNTHESIS OF HYDROTALCITE Zn-Al-SO4 AS ANION EXCHANGER AND ITS APPLICATION TO TREAT OF POLLLUTANT CONTAINED HEXACYANOFERRAT(II) - Roto Roto; Iqmal Tahir; Umi Nur Sholikhah (Indonesian Journal of Chemistry, 2008)
Synthesis of Zn-Al-SO4 hydrotalcite and its application as anion exchanger for hexacyanoferrat (II) have been studied. Synthesis of Zn-Al-SO4 hydrotalcite was carried out by stoichiometric method and hydrothermal treatment. Sulphate in hydrotalcite interlayer was exchanged by hexacyanoferrat (II) that was assumed as pollutant. Kinetics of ion exchange was also investigated. The product of ion exchange was characterized by XRD, IR spectrophotometry and atomic absorption spectrometry. Zn-Al-SO4 hydrotalcite can be obtained by stoichiometric method at pH 8 and followed by hydrothermal treatment. The chemical formula of the hydrotalcite was Zn0.74Al0.26(OH)1.74(SO4)0.13.0.52H2O. The hexacyanoferrat (II) anion could exchange sulphate in hydrotalcite interlayer as showed by IR spectra and XRD patterns. The anion exchange capacity was 645.35 meq/100 g, and the kinetics of ion exchange reaction was first order with k = 5 x 10-5 s-1. It showed that Zn-Al-Fe(CN)6  could be regenerated easily, so it has been regenerate frequently.